DESIGN OF DEFORMATION ILLUMINATION TYPOGRAPHY AS A VISUAL IDENTITY OF AMPEL ARAB VILLAGE - Ayun, Qurrota; Romadhona, Mahimma (ADBE, 2021)
Ampel Village by the people of Surabaya is known as an Arab village, because most of the population is of Arab ethnicity. The Arab village of Ampel was once the gateway to the spread of Islam in Java, especially Surabaya, which was brought by Sunan Ampel. Some residents of the Arab village of Ampel have become officials and national figures. Arab Village is also a center for Islamic education and the development of Islamic culture both past and present. The design is carried out using a qualitative approach method through interviews, observations, literature studies, as well as data analysis using TOWS Matrix Analysis to analyze the right typographic design to be used as typographic landmarks. The result of this design is a graphic environment in the form of typographical landmarks that have a visual identity and are in accordance with the characteristics of an Arab village.